Modulation of lymphocyte subpopulations by extracorporeal photopheresis in patients with acute graft-versus-host disease or graft rejection. Issue 3 (March 2015) - Lorenz, Katrin; Rommel, Katharina; Mani, Jiju; Jin, Nan; Hilgendorf, Inken; Ho, Anthony D.; Freund, Mathias; Schmitt, Michael; Schmitt, Anita
Abstract: Extracorporeal photopheresis (ECP) constitutes a promising treatment for patients with steroid-refractory acute graft-versus-host disease (aGvHD) after allogeneic stem cell transplantation and for patients with graft rejection after solid organ transplantation (SOT). There is an increasing body of evidence that modulation of lymphocyte subsets might play a crucial role in the mechanism of action in ECP. We therefore analyzed immunological effects concomitantly with clinical findings in patients under ECP therapy using multicolor flow cytometry. In a patient with steroid-refractory aGvHD and a patient with progressive bronchiolitis obliterans syndrome (BOS) after double-lung transplantation, clinical responses to ECP therapy were paralleled by an increase of CD4 + CD25hiFoxP3 + regulatory T cells and a decrease of T(EMRA) (CD3 + CD8+ CD45RA+ CD62L+ effector memory T) cells as well as of natural killer (NK)T cells. In summary, immunomonitoring of T cell subsets can elucidate the mechanism of action in ECP.